PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN SERTA KINERJA PERUSAHAAN PT. ERHA CLINIC INDONESIA - Agustini, I Gusti Ayu Ari (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The purpose of this study is to investigate the relationship between work motivation, leadership, organizational culture, employee satisfaction and its influence on the performance of the company PT. Erha Clinic Indonesia. To answer these research purposes, then an examination of the whole employees of PT. Erha Clinic Indonesia, amounting to 112 people. The method used is descriptive analysis and analysis of structural equation modeling (SEM).  Based on the results of analysis show that motivation, leadership, and organizational culture has a significant impact on job satisfaction of employees of PT. Erha Clinic Indonesia. The result of the analysis also states work motivation, leadership, organizational culture, and employee job satisfaction significantly influences the performance of the company PT. Erha Clinic Indonesia. The implications of this research is to improve leadership skills and organizational cultures that exist, so that aspects of employee job satisfaction can be met, because in general a high employee job satisfaction will increase their work motivation and performance.